2005
DOI: 10.1116/1.1885025
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetism of ultrathin Co film grown on Pt(100)

Abstract: Ultrathin Co films were deposited on Pt͑100͒ at room temperature in ultrahigh vacuum, and investigated in situ by low-energy electron diffraction, scanning tunneling microscopy ͑STM͒, and surface magneto-optic Kerr effect. The Co film was grown into a wedge shape to provide a continuous change of the film thickness. We find that the Co film forms single-crystal ultrathin films at least up to 5 monolayers ͑ML͒. For as-grown films, we observe only in-plane magnetization. After annealing the film, the Co film dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…Indeed, within the error bars, the observed maximum of µ L /µ S eff = 0.15 is found rising towards the expectations for both, ordered CoPt (µ L /µ S eff = 0.16) and CoPt 3 alloys (µ L /µ S eff = 0.19) in the easy axis of magnetization, corroborating the idea of alloy formation at these intermediate annealing temperatures. Such a finding is comparable to results from ultrathin Co films deposited on Pt(100) [ 35 ] and Pt(111) [ 36 ] single crystal surfaces, where alloying occurs between 300 °C to 400 °C. An alignment of the easy axis of magnetization should, however, be visible in the hysteresis loops discussed below.…”
Section: Resultssupporting
confidence: 83%
“…Indeed, within the error bars, the observed maximum of µ L /µ S eff = 0.15 is found rising towards the expectations for both, ordered CoPt (µ L /µ S eff = 0.16) and CoPt 3 alloys (µ L /µ S eff = 0.19) in the easy axis of magnetization, corroborating the idea of alloy formation at these intermediate annealing temperatures. Such a finding is comparable to results from ultrathin Co films deposited on Pt(100) [ 35 ] and Pt(111) [ 36 ] single crystal surfaces, where alloying occurs between 300 °C to 400 °C. An alignment of the easy axis of magnetization should, however, be visible in the hysteresis loops discussed below.…”
Section: Resultssupporting
confidence: 83%
“…Since the Co atoms were deposited after the Fe ones, one can guess the system with a thin Co layer atop the FeSi alloy. In the study of Pan et al, [63] it was observed that H c = 150 Oe for 3.6 monolayers of thin Co film, which is close to the value for the obtained system. The formation of FeCo under graphene can also be suggested.…”
Section: Magnetic Propertiessupporting
confidence: 85%
“…Magnetisation-dependent spin-orbit gaps were also observed when the system symmetry was decreased compared to the bulk symmetry. Other factors influencing the interface or bulk terms include temperature conditions (annealing [317]), the presence of surfactants (capping layers [318,319]), and the stacking sequence [320], to name a few, and hence the spin reorientation in the metallic systems also depends on each of these parameters.…”
Section: Surface Modelmentioning
confidence: 99%